Providing Higher Education in Post-Modern Times: What do University Mission Statements Tell Us about What They Believe and Do?. (March 2014) - Ellis, Jennifer; Miller, Paul
Higher education institutions (HEIs) are critical to the delivery of education for all in any nation state. What they believe and what they do are critical components to creating societal impact. But what they believe and do is not always clear. Using a derivative of SWIFT (Structured Word Identification and Frequency Totals), the authors examined the mission statements of seven HEIs in Jamaica. Using keywords, such as quality, research, and community involvement or participation, they found that some institutions had very little in common and the mission statement of a number of these HEIs do not reflect, in broader terms, the principles and goals of Education for All, as conceptualised by UNESCO in 2013. The authors conclude that whereas the HEIs in question demonstrate some affirmation of Education for All, as a whole, their mission statements do not, and therefore they need to be re-examined, and in some cases simplified, to more closely reflect global (and local) policy goals.